IMPLEMENTASI LITERASI INFORMASI GURU PENGAJAR DI MIN 10 BLITAR DALAM PENELUSURAN INFORMASI MELALUI SEARCH ENGINE GOOGLE DENGAN MODEL EMPOWERING EIGHT (E8) - Yunita Dwi Lestari; Darisy Syafaah (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2023)
This article discusses the implementation of information literacy and the obstacles experienced by teachers at MIN 10 Blitar in searching for information through the Google search engine with the empowering eight (E8) model. This research method is qualitative. The data collection uses interview, observation, and documentation techniques. Data analysis was carried out systematically, namely reducing data, presenting data, and drawing conclusions. The results of the study are that the majority of teachers already use information literacy when searching for information through the Google search engine. The eight stages of empowering eight that have not been mastered are the stages of identification, exploration, and creation. While the obstacles faced by the teacher when searching for information, namely the internet network connection at MIN 10 Blitar is still hampered and not optimal, the teacher has to repeat keywords when searching for information, the teacher does not care about the type of information source and has not included the bibliography.